The role of mental imagery in mood amplification: An investigation across subclinical features of bipolar disorders. (August 2018) - O'Donnell, Caitlin; Di Simplicio, Martina; Brown, Randi; Holmes, Emily A.; Burnett Heyes, Stephanie
Abstract: Vivid emotional mental imagery has been identified across a range of mental disorders. In bipolar spectrum disorders – psychopathologies characterized by mood swings that alternate between depression and mania, and include irritability and mixed affect states – mental imagery has been proposed to drive instability in both 'positive' and 'negative' mood. That is, mental imagery can act as an "emotional amplifier". The current experimental study tested this hypothesis and investigated imagery characteristics associated with mood amplification using a spectrum approach to psychopathology. Young adults ( N = 42) with low, medium and high scores on a measure of subclinical features of bipolar disorder (BD), i.e., hypomanic-like experiences such as overly 'positive' mood, excitement and hyperactivity, completed a mental imagery generation training task using positive picture-word cues. Results indicate that (1) mood amplification levels were dependent on self-reported hypomanic-like experiences. In particular, (2) engaging in positive mental imagery led to mood amplification of both positive and negative mood in those participants higher in hypomanic-like experiences. Further, (3) in participants scoring high for hypomanic-like experiences, greater vividness of mental imagery during the experimental task was associated with greater amplification of positive mood. Thus, for individuals with high levels of hypomanic-like experiences, the generation of emotional mental imagery may play a causal role in their mood changes. This finding has implications for understanding mechanisms driving mood amplification in bipolar spectrum disorders, such as targeting imagery vividness in therapeutic interventions.